Potential construction of the B(1)1 Π state in KCs based on Fourier-Transform spectroscopy data. (January 2015) - Birzniece, I.; Nikolayeva, O.; Tamanis, M.; Ferber, R.
Abstract: The paper presents an empirical pointwise potential energy curve (PEC) of the extensively perturbed B ( 1 ) 1 Π state of the KCs molecule constructed by applying an Inverted Perturbation Approach routine. The experimental term values in the energy range E ( v ′, J ′ ) ∈ [ 14071 ; 15502 ] cm − 1 involved in the fit were based on Fourier-Transform spectroscopy data obtained with 0.01 cm −1 accuracy from laser-induced B ( 1 ) 1 Π → X 1 Σ + fluorescence spectra in the present work (654 term values) combined with 520 term values from Birzniece et al. (2012) . The data set included vibrational v ′ ∈ [ 0, 35 ] and rotational J ′ ∈ [ 7, 233 ] quantum numbers covering about 85% of the potential well. The present fit reproduces the data included in the fit with a standard deviation 0.94 cm −1 . The empirical PEC contains an inflection at about R =4.1 Å that reflects the avoided crossing of two Ω = 1 states corresponding to B ( 1 ) 1 Π and c ( 2 ) 3 Σ + states as predicted by ab initio calculations. Abstract : Highlights: An empirical potential for first singlet Pi state of the KCs molecule was constructed. Fourier-Transform spectroscopy yielded term values with 0.01 cm −1 accuracy. Data set included vibrational levels up to v = 35 covering 85% of the potential well. The potential reproduces the fitted data with a standard deviation 0.94 cm −1 . The empirical potential contains an inflection that reflects the avoided crossing.